Shear strain rate sensitivity and crystallisation kinetics investigation in melt spun Cu64Zr36 binary metallic glass - Yipyintum, Chetarpa; Suh, Jin-Yoo; Lohwongwatana, Boonrat (Carl Hanser Verlag GmbH & Co., 2023)
Shear strain rate effect on crystallisation behaviour and characteristic temperatures of the three well-known glass formers in Cu-Zr binary amorphous system, namely Cu50Zr50, Cu56Zr44 and Cu64Zr36, were investigated. The crystallisation behaviour of Cu64Zr36 was uniquely found to be heavily dependent on shear strain rate. Crystallisation kinetics were studied through Isochronal transformation and isothermal transformation. The activation energy of crystallisation of each case was compared and contrasted. Johnson-Mehl-Avrami (JMA) analyses were also employed to study its kinetics behaviour. Finally, high angle annular dark field (HAADF) scanning transmission electron microscopy (STEM) combined with laser-assisted local electrode atom probe (LEAP) investigation revealed no detectable clustering or phase separation.